The Effect of Work Posture on Work Fatigue in Furniture Workers in the East Jakarta Furniture Industry Center - Iwan Jaya Azis; Nur Asniati Djaali; Brian Sri Prahastuti (CV. Publikasi Indonesia, 2024)
Indonesia's Micro, Small, and Medium Enterprises sector in 2022 will reach 9.1 million. One of the MSMEs developing in Indonesia is furniture at the East Jakarta Furniture Industry Center. Based on researchers' observations of furniture workers at the East Jakarta Furniture Industry Center, many workers still work without personal protective equipment, and the working environment conditions are poor. Testing has been carried out. In tidying work activities such as sanding, the worker's body posture can cause work fatigue, which causes accidents and work-related illnesses that cause losses. They are proving the effect of work posture on work fatigue of furniture workers in the furniture industry center. This research design was cross-sectional, and the sample size in this study was 127 respondents, with data collection using a reaction timer and questionnaire. Data analysis uses univariate tests, bivariate tests, and multivariate tests. Multivariate analysis results show that work posture factors (p=0.002) have an influence on work fatigue after being controlled by work climate factors (p=0.012), history of illness (p=0.06), and workload (p=0.09) with a value of 0R = 4.061. Entrepreneurs/employers should provide short chairs, drinking water, and exhaust fans, conduct regular health checks, and regulate workload. The government strengthens labor supervision and makes regulations that require periodic health checks and company compliance to participate in BPJS.